Favorable outcome of total hip arthroplasty with insufficient bone coverage of the roof reinforcement ring - Judas, F (2015)
INTRODUCTION: Total hip arthroplasty in patients with developmental dysplasia of the hip can be a complex procedure due to acetabular and proximal femoral deformities. PRESENTATION OF CASE: A 59-year-old male patient underwent a total hip arthroplasty for the treatment of end-stage dysplastic osteoarthritis. A roof reinforcement ring, a cemented polyethylene cup, and a cementless stem were used. A portion of the superior rim of the ring was uncovered by the host bone. Morsellized autogenous femoral-head graft was impacted to fill the space between the superior rim of the ring and the superior part of the dysplastic acetabulum. At the follow-up after 5-years, the patient had no complaints and was very satisfied with the operation result. The hip radiograph revealed no signs of instability of the acetabular component, and no bone graft resorption. DISCUSSION: Favorable results were described using metal rings and conical femoral stems for the treatment of the developmental dysplasia of the hip. The superior rim of the metal ring should be against host bone for 60% of its support. Despite the suboptimal implantation of the ring compromising, apparently, mechanical stability of the arthroplasty, the outcome was favorable. CONCLUSION: This result can be supported by the good fixation of the metal ring to the pelvis with screws, the adequate orientation of both components of the total hip arthroplasty, and the bone graft incorporation.